Leftamap Kastom: The Political History of Tradition on Tanna, Vanuatu - Lindstrom, Lmqnt (The Australian journal of anthropology, 1982)
The history of evaluation and definition of kastom on Tanna exemplifies its utility in attempts to reformulate social groups by reworking group charter myths, and its manipulation in political events by rival organizations seeking a customary legitimacy. On Tanna, where political prestige and authority depend heavily on the control and communication of knowledge, kastom knowledge as political capital enjoys enhanced status following the rehabilitation of kastom at the national level. Pro-kastom groups on Tanna, such as the John Frum cultists, have benefited from this positive evaluation of kastom, but some anomalies and sources of conflict remain in the fusion of kastom with Christianity and modernism. People argue over their respective domains and the fields of their application. Alternate definitions and uses of kastom invoke disunity and political competition at the local level, in contrast to national emphases on kastom as symbol of political unity and shared identity.